Taxation, work and gender equality in Ireland - Doorley, Karina (Statistical and Social Inquiry Society of Ireland, 2018)
In most developed countries, economies are facing population ageing, falling fertility rates and stagnating labour force participation. The ability of governments to fund future pension and health-care expenditure relies to a large extent on income tax and social security receipts from workers. Policymakers are generally in agreement that increasing the labour force participation of women, without reducing the fertility rate, is needed. In the year 2000, with the aim of increasing women’s labour market participation, a partial individualisation of the Irish income tax system was initiated. Using the Living in Ireland survey and a difference-in-differences framework, I investigate whether this reform had any effect on female labour supply and caring duties. I find that the labour force participation rate of married women increased by 5-6 percentage points in the wake of the reform, hours of work increased by two per week and hours of unpaid childcare decreased by approximately the same margin.
read before the Society, 25 January 2018, Barrington Lecture 2017-18
Keywords: Individual taxation; labour supply; Ireland; 314.15